Integrity Issue on Grab Drivers' Fraud Phenomenon - Gita Yuniar; Puji Handayati; Sheila Febriani Putri (AIBPM Publisher, 2020)
Recent development of technology undeniably and rapidly goes into orbit. Internet technology turns out to be a media to simplify anyone's work. Along with its developments and the service industry revolutions, a new breakthrough has emerged, namely smartphone app-based ride-hailing services. This eliminates the problems existing in conventional services, such as the difficulty of finding rates, uncertain rates and passenger safety guarantee. This study aims to describe the fraud committed by the Grab drivers and its impact for the drivers and Grab, and how to overcome it. This study uses qualitative research with a phenomenological approach. The object of this research is Grab drivers in Malang. The data used are primary and secondary data obtained through interviews, Application screenshots, and news items. The results of this study indicate that there are some frauds committed by Grab drivers such as (1) fictitious orders, (2) account sales, (3) account leases. To anticipate it, Grab has initiated a program namely